Peningkatan Ketahanan Pangan Masyarakat Sekitar Hutan di KHDTK Mungku Baru di Masa Pandemi Covid-19 - Nanang Hanafi; Pienyani Rosawanti; Fahruni Fahruni; Fahruddin Arfianto; Nurul Hidayati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Hydroponics is a method of growing crops without using soil media but with a nutrient solution of minerals or other materials. The media used includes household waste, such as used bottles, buckets, hoses, pots, paralon, stove wicks, and other household items. This technique can be applied to the yard of the house to produce vegetables for the family. The purpose of the service is that the Mungku Baru Village Community can optimize their yards for agricultural crop cultivation using a floating raft hydroponic system and duck bucket to improve food security during the Covid-19/post-covid-19 pandemics. The activity was carried out in Mungku Baru Village, Rakumpit District, Palangka Raya City in August 2020. The method of this activity is by way of counseling and workshops or extension activities, and the practice of making simple hydroponics statically, namely by explaining simple hydroponic cultivation techniques directly and demonstrating them, and activity participants are given simple hydroponic cultivation pamphlets as a guide to hydroponic techniques in their homes. As a result of this activity, the community has prepared a hydroponic place, followed by preparing plant life media, sowing seeds, planting seeds, and making hydroponic solutions directly. They know the dosage of using the hydroponic nutrient solution in its application. The community cultivates vegetables with a simple hydroponic method placed on the terraces and yards of the house with vegetables that are easy to grow, harvest quickly, and easy to maintain.